PERSEPSI SISWA TERHADAP IKLIM SEKOLAH: STUDI KASUS SCHOOL WELL BEING SISWA SMP DIDAERAH 3T (TERLUAR, TERPENCIL TERDEPAN) - Mbado, Yasni Febiwanti; Ama, Roy Gustaf Tupen (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to find out students' perceptions of School Climate: A Case Study Of School Well Being Junior High School Students In 3t Regions (Outside, Front Remote). To achieve the research objectives, researchers used quantitative methods and selected 150 students of SMP 'X' in Rote as samples. This research uses a purposive sampling technique. The characteristics of the participants in this study consisted of junior high school students, male and female, aged 12–16 years and attending school in the 3T (outermost, remote, foremost) area of ​​Rote, East Nusa Tenggara. The measuring instruments used in this research are the school climate perception scale which refers to Konold's theory and the school well being scale which refers to Konu & Rimpela's theory. The data was analyzed using the Pearson product moment correlation technique to determine the relationship between the variables studied. The research results show that there is a substantial positive relationship (F = 147.068, Partial Eta Square = 0.497, and p = 0.000 (p < 0.05)) between students' perceptions of school climate and school well being. The effective contribution of school climate perceptions to school well being is 49.7%. The implication of this research is that the issue of school well being can be paid attention to and improved for educational purposes, especially in the 3T area so that students can learn well and produce brilliant achievements.